CRYOGENIC PROCESSES - Sergey M. GOVORUSHKO (Editura Universitaria Craiova, 2011)
Cryogenic processes are quite numerous, but among them the most significant, from the viewpoint of inﬂuence on human activities, we mention frost swelling, thermokarst processes, thermal abrasion, thermal erosion, cryogenic cracking, and soliﬂuction. Frost heaving represents a danger for motor roads, railroads and airﬁelds, communication and transmission lines, bridges, and other structures. Thermokarst endangers the safety, stability, and normal operation of structures. Thermoabrasion affects industrial and civil site development, water transport, pipeline transport, mineral resource industry, hydropower engineering, and agriculture. Frost cracking constitutes a certain danger for the following engineering structures: motor roads (roadways may go over the discontinuity); residential and industrial buildings (breakage of continuous footings, cracks in the walls); airfields (damage to airfield pavements); pipelines (deformations and even breaks of underground steel pipelines); underground communication cables. The inﬂuences of fast and slow soliﬂuction are the most urgent for the following kinds of human activity: mineral resource industry; transport (motor, rail, pipeline); and industrial and civil engineering. Thus, the present paper aims at rendering the global dimension of these processes stressing their consequences worldwide.